The Politics of Profits: Profit Squeeze and Political-Economic Change in Sweden, 1975–85 - Bengtsson, Erik (Journal of Contemporary History, 2025)
In the mid- to late 1970s, the Swedish economy faced a profit squeeze which threatened to hamper investments and the creation of jobs. This engendered a massive debate in the media and among economists and policymakers. This article investigates what I call ‘the politics of profits, the debates around the role of corporate profits in a democratic capitalist society and economy and the policy measures directed towards manipulating the distribution between capital income and labour income. The Swedish political economy from the mid-1970s to the mid-1980s presents an important case in that the mid-1970s saw labour movement radicalization and proposals for socialization of investment, but the outcome by the mid-1980s was rather a move toward greater emphasis on stock saving and raising capital via the capital markets, that is ‘financialisation’. The contradictory history of the period sheds new light on the much-discussed shift from a social democracy postwar period to a more market liberal economy in the 1980s and 1990s.